NUMERICAL MODEL OPTIMIZATION FOR TSUNAMI WAVE PROPAGATION - Adam, Grace
Tsunamis are a phenomenon of large-amplitude, high-velocity waves generally caused by undersea earthquakes. This phenomenon often causes significant material damage and loss of life. To accurately simulate this phenomenon, mathematical models must be able to capture the non-linearity and dispersive nature of waves. Therefore, the Boussinesq Model is used in this study. Two numerical approaches, namely Mohapatra-Chaudhry Modification and Finite Volume on a Half Grid, are considered to solve the Boussinesq equation. However, limitations in capturing the wave phase velocity motivated the merging of the two numerical schemes. In addition to the coupling, model optimization is performed by adding two epsilon parameters to determine the weight values of the optimized Boussinesq terms using Genetic Algorithm. The simulation results of the developed scheme will be compared with Hammack's experimental results to evaluate their accuracy. Hammack's experiment involves seafloor deformation to generate tsunami waves. Furthermore, this numerical scheme will be used to conduct a sensitivity analysis of the impact of plate width and maximum plate movement from Hammack's experiment on the Coastal Vulnerability Index value.